Role of factors influencing on anaerobic process for production of bio hydrogen: Future fuel - Ravuri, Hema krishna (International Journal of Advanced Chemistry, 2013)
The process of anaerobic treatment is indeed more complex than the aerobic systems, and for this reason, the operation of an anaerobic treatment system should have a solid understanding of the important factors like temperature, pH, bicarbonate alkalinity, VFA, inorganic salts, sulfide soluble salts, in operation, heavy metals and nutrient requirement, in operation and control and are associated with the stability of the biological process involved. Thus the review was directed especially to these.